Clinicopathological features associated with CD44 and CD63 expression in breast cancer - Castaneda, CA (2024)
Background: CD44 is a cell-surface transmembrane glycoprotein that participates in the regulation of many cellular processes, including cell division, adhesion, migration and stem-like characteristics. CD63 is involved in the exocytosis process. Objective: To evaluate the relationship between CD44 and CD63 expression and clinicopathological features, including tumor-infiltrating lymphocytes (TILs), phosphoinositide 3-kinase (PIK3CA) mutation and survival. Methodology: CD44 and CD63 were stained in samples from 101 breast cancer cases from Peruvian women. Results: Median age was 52 years, most were most were grade-3 (68%), estrogen receptor (ER)+ (64%) and stage II-III (92%). Median ki67 was 30%, median stromal TIL was 30% and PIK3CA mutation was found in 49%. Longer survival was associated with earlier stages (p = 0.016), lower ki67 (p = 0.023), ER+ (p = 0.034), luminal phenotype (p = 0.029) and recurrence (p < 0.001). CD44 was classified as high cell density staining in 57% and high intensity in 55%. High CD44 density was associated with younger age (p = 0.043), triple-negative phenotype (p = 0.035) and shorter survival (p = 0.005). High CD44 expression was associated with short survival (p = 0.005). High CD63 cell density was found in 56% of cases and was associated with ER-positive (p = 0.045), low TIL levels (p = 0.007), Luminal-A (p = 0.015) and low CD44 intensity (p = 0.032). Conclusion: CD44 expression was associated with aggressive features and low CD63 density staining.